MENINGKATKAN KEMAMPUAN MENJUMLAHKAN BILANGAN BULAT 1-10 BAGI ANAK TUNAGRAHITA RINGAN MELALUI MEDIA TANGGA BILANGAN - Herman - (Universitas Negeri Padang, 2015)
This study was motivated by the problems that I have found on a mild mental retardation children sitting in class IV C SLB fan-redha Padang. The child is experiencing problems of summation, aims to improve the ability of the sum of integer numbers 1-10 through the media ladder. This study uses a Single Subject Research approach, using AB design and data analysis techniques using visual analysis chart. Subjects were mild mental retardation children fourth grade. Results of analysis of data on baseline conditions (A) shall not exceed six kalipertemuan with the results of 20%, 10%, 0%, 20%, 20%, 20%. A second session interventions (B) observations were made eight times the media ladder observations using numbers as 30%, 50%, 60%, 70%, 70%, 80%, 80%, and 80%. It can be concluded that, the media ladder can improve the ability of the sum of the number of integers 1-10 in children Tunagrahita light in SLB fan-redha Padang. is recommended for teachers to implement the media ladder numbers to increase understanding and summing the mild mental retardation children in mathematics. Kata kunci : Menjumlahkan Bilangan Bulat 1-10, Media Tangga Bilangan, anak tunagrahita ringan, SLB Fan-Redha Padang.